Analisis Kualitas Butir Soal Penilaian Akhir Semester Mata Pelajaran Seni Budaya di SD Shibghah Akhlak Qur’an Bekasi - Hilmiyah Ridwan; Sigit Muryono (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Evaluation ensures that the teaching and learning processes align with the desired objectives by using test items (instruments) to measure students' competency progress. Initial observations indicate that the test items in the semester-end exams have not undergone thorough analysis, resulting in unknown quality. This study examines the quality of the semester-end test items for the Art and Culture subject for 11th-grade students at SD Shibghah Akhlak Qur’an Bekasi in the 2024/2025 academic year, considering difficulty level, discrimination power, and distractor effectiveness. The researchers employed a descriptive quantitative method to analyze the test items' quality. The sample included 72 students, with data collected through documentation and interviews, and analyzed using ANATES V4 and Microsoft Excel. The results showed that out of 40 test items, 10% were of very high quality and retained, 17.5% were good, 45% were satisfactory and archived for revision, 12.5% were poor, and 12.5% were very poor and thus deleted or replaced. Overall, the analysis of the test items indicates many items are not optimal, necessitating improvements and revisions in test items to ensure more accurate and meaningful evaluation outcomes.